Pathological femoral fractures due to osteomalacia associated with adefovir dipivoxil treatment for hepatitis B: a case report - Tanaka Motoyuki; Setoguchi Takao; Ishidou Yasuhiro; Arishima Yoshiya; Hirotsu Masataka; Saitoh Yoshinobu; Nakamura Shunsuke; Kakoi Hironori; Nagano Satoshi; Yokouchi Masahiro; Kamizono Junichi; Komiya Setsuro (BMC, 2012)
Abstract We present a case of a 62-year-old man who underwent total hip arthroplasty for treatment of pathologic femoral neck fracture associated with adefovir dipivoxil-induced osteomalacia. He had a 13-month history of bone pain involving his shoulders, hips, and knee. He received adefovir dipivoxil for treatment of lamivudine-resistant hepatitis B virus infection for 5 years before the occurrence of femoral neck fracture. Orthopedic surgeons should be aware of osteomalacia and pathological hip fracture caused by drug-induced renal dysfunction, which results in Fanconi's syndrome. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1600344696739249